2021
DOI: 10.3390/metabo11120831
|View full text |Cite
|
Sign up to set email alerts
|

Walker-256 Tumour-Induced Cachexia Altered Liver Metabolomic Profile and Function in Weanling and Adult Rats

Abstract: Cancer cachexia occurs in up to 85% of advanced cancer patients, affecting different tissues and organs, mainly the liver, which plays a central role in body metabolism control. However, liver responses to cancer cachexia progression are still poorly understood. Considering the possible different challenges provided by the rodent’s phase of life and the cachexia progression, we evaluated the liver metabolic alterations affected by Walker-256 tumour growth in weanling and young-adult rats. For this, we applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…We also observed a decrease in the tumor mass of rats treated with L-glutamine, but this reduction was not significant. In a study with liver cancer, the authors also found no changes in tumor weight 4 ; however, in a previous study conducted by our research group, a significant reduction in tumor mass was observed due to L-glutamine supplementation in the rats with tumor 31 .…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…We also observed a decrease in the tumor mass of rats treated with L-glutamine, but this reduction was not significant. In a study with liver cancer, the authors also found no changes in tumor weight 4 ; however, in a previous study conducted by our research group, a significant reduction in tumor mass was observed due to L-glutamine supplementation in the rats with tumor 31 .…”
Section: Discussionmentioning
confidence: 48%
“…Weight loss is higher in cancer patients, as tumors cause excessive energy consumption and generate energetic inefficiency, being accountable for an increase in the glucose usage, and a depletion in intramuscular and hepatic glycogen 4,31 . The loss of body mass in cachexia is related to reduced muscle and adipose mass due to inadequate neurohormonal anabolic activity and/or excess catabolic activity [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miyaguti et al [11] reported higher lipid metabolites and impaired mitochondrial CII and CIV complexes in Walker 256 tumor bearing animals this impairment in liver metabolism was more pronounced in weanling than adult animals.…”
Section: Findings In Liver (Animal Studies Only)mentioning
confidence: 93%